1986
DOI: 10.1016/s0165-5876(86)80042-8
|View full text |Cite
|
Sign up to set email alerts
|

Mucociliary function and nasal resistance evaluation before and after adenoidectomy

Abstract: Thirty-four children with clinically and radiologically confirmed adenoid hypertrophy underwent otoscopy, impedance tests, active anterior rhinomanometry and nasal mucociliary clearance evaluation before and 6 months after adenoidectomy. Mucociliary clearance velocity increased significantly while binasal resistances decreased after surgery. The authors conclude that mucociliary evaluation and objective measurements of nasal resistances should be added to impedance tests as indicators to adenoidectomy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…As a final point, reduced mucociliary clearance has been demonstrated in patients with adenoid hypertrophy (29), with improvement noted after adenoidectomy [30]. Impaired mucociliary clearance may enhance sensitivity to upper and lower respiratory tract infections due to the extended presence of microorganisms on the respiratory mucosa and because of the existence of factors that hinder the capacity to protect against microbial colonization and invasion.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…As a final point, reduced mucociliary clearance has been demonstrated in patients with adenoid hypertrophy (29), with improvement noted after adenoidectomy [30]. Impaired mucociliary clearance may enhance sensitivity to upper and lower respiratory tract infections due to the extended presence of microorganisms on the respiratory mucosa and because of the existence of factors that hinder the capacity to protect against microbial colonization and invasion.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Our findings suggest that pediatric patients with AH have an acquired, temporary disorder of CBF, which is improved after adenoidectomy to the level of healthy children. Increased nasal CBF after surgery could explain the postoperative improvement of nasal MCV and MCT recorded in previous studies . We suppose that acquired (secondary) ciliary dyskinesia, observed in children with AH, could contribute to the pathogenesis of RRI in these patients by negatively affecting mucociliary clearance and creating a local environment that promotes further development of infection.…”
Section: Discussionmentioning
confidence: 73%
“…Its efficiency is affected by the viscoelastic properties of mucus as well as by the coordinated movement of respiratory cilia—particularly their beating pattern and frequency . In previous studies, reduced nasal mucociliary clearance velocity (MCV) and higher nasal MCT were observed in children with AH using the saccharine test, while 1 month and 6 months after adenoidectomy, these parameters were significantly improved and reached the values of healthy children …”
Section: Discussionmentioning
confidence: 97%
“…Although this association seems logical, it has failed to be proven in several studies looking at the volume [19] or weight [17] of the adenoid tissue removed, as well as radiographic evidence of nasopharyngeal obstruction by adenoid hypertrophy [20]. Finally, impaired mucociliary clearance has been identified in patients with adenotonsillar hypertrophy [21] with improvement noted after adenoidectomy [22] or adenotonsillectomy [21].…”
Section: Discussionmentioning
confidence: 99%